3D Thermal Finite Element Analysis of the SLM 316L Parts with Microstructural Correlations. (3rd October 2018) - He, Ketai; Zhao, Xue
Abstract : In this study, a multitrack and multilayer finite element model was developed to simulate the temperature field and molten pool contours during selective laser melting (SLM) of 316L stainless steel powder under different scanning strategies. The simulated temperature field and its evolution over time were compared with experimental measurement results. Furthermore, a correlation was established by the presented results between the predicted thermal behavior and the microstructure of SLM specimens. It was found that the maximum temperature of the molten pool rose slightly with the increase of scanning tracks, but when laser scanned multilayer, the maximum temperature rose first and then decreased. There are large columnar crystals in molten pools, growing in the direction of the maximum temperature gradient. The microstructure defects are more likely to occur at the bonding regions between adjacent layers and islands, where the heat and stress are concentrated. Moreover, the results also showed that the scanning strategy affects the microstructure and microhardness. Also, the SLM 316L parts under the S-shaped strategy had finer grains and a higher Vicker hardness than that formed under the island strategy.